Wealth inequality and entrepreneurial activity in South Africa: Evidence from the National Income Dynamics Study - Sibanda, Numbulelo (My University, 2019)
There is currently little empirical research exploring the interaction of wealth inequality, in particular, and entrepreneurship. South Africa is one of the most unequal countries in relation to net wealth distribution. The purpose of this study is to ascertain the relationship between wealth inequality and entrepreneurial activity in South Africa. Establish the nature of this relationship for individuals at the top of the wealth distribution (wealthy individuals) in contrast to those at the bottom (poor individuals) of the wealth distribution. A quantitative research design is used and a fixed effect model was estimated to test this studies hypotheses. A balanced sample from the National Income Dynamics Study (NIDS) survey was used and it covers all individuals in the geographic location of South Africa. This study finds evidence suggesting that amidst low levels of entrepreneurial activity, at an aggregate level, there is a positive relationship between wealth inequality and entrepreneurial activity in South Africa. It also finds evidence that suggests that this relationship is not significant across the entire wealth distribution, and in particular, it is not significant for the top end of the distribution (wealthy individuals). The relationship between casual labour and wealth inequality is also significant and positive at an aggregate level. Wealth inequality is high but the rate of entrepreneurial activity is still low by international standards. This means that a wider range of interventions need to put in place to improve entrepreneurial propensity in this country. This study has contributed to literature by bridging the gap between development economics and entrepreneurship by investigating the association between dimensions in both disciplines instead of one or the other in isolation. Furthermore it provided evidence to establish the type of relationship that exists between wealth inequality and entrepreneurial activity in South Africa.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management in Entrepreneurship and New Venture Creation
Keywords: Wealth--South Africa; Equality--Economic aspects; Income distribution--South Africa